A study on the macroscopic self-organized structure of high-power millimeter-wave breakdown plasma. (28th July 2020) - Oda, Yasuhisa; Takahashi, Masayuki; Ohnishi, Naofumi; Komurasaki, Kimiya; Sakamoto, Keishi; Imai, Tsuyoshi
Abstract: Air breakdown plasma induced by a strong electromagnetic (EM) wave field with a millimeter wavelength has a self-formed filamentary structure. The scale of the breakdown plasma is much larger than the wavelength scale, and the power density is lower than the self-ignition threshold of atmospheric breakdown. We observed a breakdown plasma that consisted of small plasma spots, and their trajectory was identical to that of the filamentary structure observed macroscopically. The numerical analysis showed that the interaction of the ionization front, EM field, and neutral-gas heating determines the self-organized structure of the branching plasma. The plasma trajectory identified in the analysis was identical to that of the experimental results. This novel physical process was entirely different from the discrete filament formation observed in the breakdown plasma formed under a focused beam, and the physical process of the breakdown strongly depended on the scale and power density.